2006
DOI: 10.1159/000121368
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Improves Spatial Cognitive Ability in Mice

Abstract: Although it has been reported in a lot of studies that hypoxic preconditiong could protect the brain from hypoxic/ischemic injury, it is not clear whether hypoxic preconditioning could affect brain functions such as cognitive ability. This work aims at investigating the effect of hypoxic preconditioning on spatial cognitive ability in mice after acute and repeated hypoxic exposures. The mice were randomly divided into 3 groups: a control group in which mice were not exposed to hypoxia (H0) and experimental gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…Whereas another study reported that hypoxia can improve memory in normal animals [22], we found that normal rats showed no significant enhancement of either spatial learning and memory or newborn cell activity following IH. This inconsistency may reflect the use of a different learning and memory task, BrdU dose and injection protocol, and species.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas another study reported that hypoxia can improve memory in normal animals [22], we found that normal rats showed no significant enhancement of either spatial learning and memory or newborn cell activity following IH. This inconsistency may reflect the use of a different learning and memory task, BrdU dose and injection protocol, and species.…”
Section: Discussioncontrasting
confidence: 99%
“…The procedure of hypoxic experiment was performed as previously described [9]. The mice were placed into a 125 mL jar with fresh air, which was sealed with a rubber plug.…”
Section: Methodsmentioning
confidence: 99%
“…After sacrifice, the brain was quickly removed and placed in ice-cold, oxygenated artificial cerebrospinal fluid (ACSF) for about one minute. The hippocampal slices were prepared essentially as previously indicated [9]. Freshly prepared slices were maintained in ACSF at room temperature for at least 3 h before recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for hypoxic exposure was performed as previously described [ 17 ]. Briefly, the male mice were placed into a 125 mL jar with fresh air, and the jar was sealed with a rubber plug.…”
Section: Methodsmentioning
confidence: 99%